Online determination of phycocyanin in vivo in Galdieria sulphuraria - Philipp Scherhag; Michael Katzberg (Applied Phycology)
The extremophilic red alga Galdieria sulphuraria is well known for its metabolic capabilities with respect to organic carbon sources as well as its ability to produce the blue pigment phycocyanin (PC). The interest in PC as natural food colourant as well as nutraceutical is growing steadily. Therefore, a reliable quantification of PC accumulated by G. sulphuraria is crucial for establishing a production process. PC can be quantified through photometry but only after a laborious extraction procedure, which reduces the amount of data that can be gained from a cultivation. Hence, a faster PC determination method, with the potential to become an online method, is needed. In this study, we present a fast method for estimating the specific PC concentration based on in vivo absorbance spectra from cells of G. sulphuraria. A correlation with the PC concentration in the raw extract could be obtained, resulting in a 10-fold cross-validated coefficient of determination cR2 = 0.951. This makes extraction unnecessary in most cases. Especially in small-scale cultivation, where usually the available amount of biomass limits the number of measurements, this method presents a viable alternative to the extraction of PC.